2021
DOI: 10.3390/rs13040657
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Snow Depth Data at Moderate Spatial Resolution (1 km) from Remotely Sensed Snow Data and Multiple Optimized Environmental Factors: A Case Study over the Qinghai-Tibetan Plateau

Abstract: Snow depth distribution in the Qinghai-Tibetan plateau is important for atmospheric circulation and surface water resources. In-situ observations at meteorological stations and remote observation by passive microwave remote sensing technique are two main approaches for monitoring snow depth at regional or global levels. However, the meteorological stations are often scarce and unevenly distributed in mountainous regions because of inaccessibility, so are the in-situ snow depth measurements. Passive microwave r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 71 publications
0
12
1
Order By: Relevance
“…Such frequently examined areas, which are not only covered as part of large-scale studies, but examined specifically, are for instance the Great Plains in North America [73,[82][83][84][85][86][87], sometimes as part of studies covering Central North America [46,75,[88][89][90][91][92], or the USA [93][94][95][96][97][98][99]. Another often-applied study area is the Tibetan Plateau in Asia [100][101][102][103][104][105], also sometimes as part of studies conducted over High-Mountain Asia (HMA) [106][107][108][109]. Also often examined is the Mackenzie-Basin in Canada [110][111][112][113][114] or Northwestern China [63,[115][116][117][118][119][120].…”
Section: Spatial and Temporal Distribution Of The Examined Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Such frequently examined areas, which are not only covered as part of large-scale studies, but examined specifically, are for instance the Great Plains in North America [73,[82][83][84][85][86][87], sometimes as part of studies covering Central North America [46,75,[88][89][90][91][92], or the USA [93][94][95][96][97][98][99]. Another often-applied study area is the Tibetan Plateau in Asia [100][101][102][103][104][105], also sometimes as part of studies conducted over High-Mountain Asia (HMA) [106][107][108][109]. Also often examined is the Mackenzie-Basin in Canada [110][111][112][113][114] or Northwestern China [63,[115][116][117][118][119][120].…”
Section: Spatial and Temporal Distribution Of The Examined Studiesmentioning
confidence: 99%
“…Moreover, it becomes apparent that the commencement of coverage frequently coincides with the launch of specific sensors. In addition to the aforementioned SMMR in 1978 (n = 10), this mainly applies to the Special Sensor Microwave/Imager (SSM/I, n = 10) in 1987 [91,109,140,159,167,185,188,189,[194][195][196][197], the Advanced Microwave Scanning Radiometer for Earth Observation (AMSR-E, n = 27) [61,82,88,101,107,110,111,129,131,137,142,[150][151][152]155,156,158,162,[172][173][174][175]177,179,198,199], and the Advanced Microwave Scanning Radiometer 2 (AMSR-2, n = 4) [103,126,200,201]. The average coverage duration is just under 9.5 years with the longest study covering 41 years (1978-2019) [123], while some studies only examine a few months or one winter season…”
Section: Designationmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the annual tree ring index to reconstruct snow data can provide important reference information for understanding the history of changes in snowfall and predicting future ones [21]. Existing studies have shown a correlation between radial tree growth and snowpack [22][23][24][25], and reconstructions of snowpack metrics, such as snow depth and snow days, have been performed based on these data [18,[26][27][28][29][30][31]. However, only a limited number of studies have been conducted in Central Asia, and most of these studies were based on the results of analyses acquired from a relatively small number of sampling points and limited meteorological material.…”
Section: Introductionmentioning
confidence: 99%
“…Historical studies have indicated that snow is a key factor contributing to avalanche occurrences along the Pemo Highway [13][14][15][16]. Therefore, it is of great significance to assess avalanche susceptibility with snow as the main conditioning factor after obtaining the spatial and temporal characteristics of the snow cover along the Pemo Highway.…”
Section: Introductionmentioning
confidence: 99%